Cartografia do JÁ sob a ótica dos gêneros jornalísticos: análise do diário paraibano e o debate sobre gêneros na atualidade - Andrade, Amanda Carvalho de (2015)
The newspapers turned to the popular classes are a reality across the country and, each year, are consolidating in the national and regional press. In Paraíba, only one newspaper follows the line of such news, the JÁ. These kind of daily are changing the design of sensationalism in order shoddy journalism, exaggerations and even untrue news. Our work drew a map of the JÁ in order to investigate the newspaper, from the contributions of journalistic genre studies, especially with the support of contributions proposed by Lia Seixas. Thus, it was possible to trace the journal profile from the analysis of the construction of your news, especially considering their connection with the categories of analysis proposed. We resume the debate on journalistic genres from the literature of José Marques de Melo, Lia Seixas, Manuel Chaparro, Francisco de Assis, among others. During the work, we discuss the concepts of popular journalism and sensational, the history of this kind of journalism, the criteria of newsworthiness and processes and production phases of sensational news. The methodology used was the content analysis and the proposed codification of genres from Lia Seixas of 12 issues in the week 11th to 16th May 2009, the first week of circulation of JÁ, and 24th to 29th March, 2014, an latest week during the analysis period, randomly chosen. The analytical approach was the editorial Cidades and Super Notas. From the analysis of 128 news, we could identify the building strategies of the news from the techniques and established practices of the current journalism.